Carbon nitride creates thioamides in high yields by the photocatalytic Kindler reaction. Issue 4 (6th February 2018) - Kurpil, B.; Kumru, B.; Heil, T.; Antonietti, M.; Savateev, A.
Abstract : Potassium poly(heptazine imide), a carbon nitride based photocatalyst, effectively promotes the Kindler reaction of thioamide bond formation using amines and elemental sulfur as building blocks under visible light irradiation. Abstract : Potassium poly(heptazine imide), a carbon nitride based photocatalyst, effectively promotes the Kindler reaction of thioamide bond formation using amines and elemental sulfur as building blocks under visible light irradiation. The feasibility of the developed methodology was confirmed using 14 different primary and secondary amines, including substituted benzylamines and heterocyclic and aliphatic methylamines, which were successfully converted into thioamides with 68–92% isolated yields.